International Monetary Fund Annual Report 2021 Financial Statements. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 2021)
The audited financial statements that follow form Appendix VI of the International Monetary Fund's Annual Report 2021 and can be found, together with Appendixes I through V and other materials, on the Annual Report 2021 web page (www.imf.org/AR2021). They have been reproduced separately here as a convenience for readers. Quarterly updates of the IMF's Finances are available at www.imf.org/external/pubs/ft/quart/index.htm.